Professional development of teachers in the function of developing interculturality - Purić Daliborka S. (University of Kragujevac - Faculty of Pedagogy, Užice, 2017)
Changes in the global plane and heterogeneity of modern societies in national, linguistic, religious and other terms have resulted in the affirmation of interculturalism and the need for intercultural education. In this process, a modern school, as a place of meeting of national and global culture, plays an important role in establishing dialogue among different cultures, thus enabling their coexistence. Education for diversity as the basis for the development of a multicultural society should be incorporated in the programs of education and professional development of teachers, within which they can acquire knowledge about the distinctive features of the cultural origin of their pupils, as well as the skills they need to translate that knowledge into effective teaching. The author in the paper examines the possibilities of training teachers in the function of encouraging interculturality within the framework of professional training programs in Serbia. The results of the research show that the programs of professional development of employees in education open the possibility of acquiring basic knowledge and skills in the domain of interculturality. Systemic monitoring of the needs of the modern educational system and modern society is lacking, which is why intercultural activity is essentially left to the good will and commitment of individual teachers, and not to the care of society as a whole.